Adsorption study of modified coal fly ash with sulfonic acid as a potential adsorbent for the removal of toxic reactive dyes from aqueous solution: Kinetics and thermodynamics. Issue 5 (October 2018) - Dash, Subhajit; Chaudhuri, Haribandhu; Gupta, Radha; Nair, Udayabhanu G.
Abstract: Great emphasis is being put in to develop green, efficient and inexpensive adsorbent in recent years. In this study, we demonstrate the potential of coal fly ash (CFA) materials as environmental pollutant adsorbent. The Sulfonic acid functionalized heat and alkali treated CFA (HATF-SO3 H), is synthesized by condensation of 3-mercaptopropyltrimethoxysilane (3-MPTS) and heat and alkali treated CFA (HATF) followed by oxidation of surface thiol groups by H2 O2 to sulfonic acid groups. The as-synthesized product is used to remove toxic and reactive dyes i.e. Malachite green (MG) and Rhodamine 6G (R6G), which are the main contaminant from the dye manufacturing and textile finishing. The efficiency of the dye adsorption on HATF-SO3 H surface was investigated under various experimental parameter such as adsorbent dose, contact time, stirring speed, pH, and temperature. The proficient sorption efficacy of HATF-SO3 H q m towards toxic and reactive dyes (efficiency of MG removal, 99.20%; maximum specific removal q m 233.30 mg g −1 : efficiency of R6G removal, 98.70%; maximum specific removal 381.70 mg g −1 ) can be explained from the perspective of both electrostatic and H-bonding interactions between the surface of HATF-SO3 H and dye molecules.